Learning Situation Analysis For Hotel Accommodation Students’ At Vocational High School - Annisa, Annisa; Sevrika, Hevriani; Sani, Riny Dwitya (JUPE : Jurnal Pendidikan Mandala, 2023)
English is a language that is needed by many people, one of which is vocational high school, especially hotel accommodation students. Based on pre-observation, it was found that there are still many students who have difficulty speaking English. For this reason, this research was conducted with the aim of analyzing the desire of hotel accommodation students in learning English by using qualitative descriptive methods and random sampling to determine the respondents. The respondents of this study were 22 students of class XI hospitality accommodation (Ph2). Researchers collected data by distributing questionnaires to students. The stages that researchers use to analyze data are Reading, Describing, Classifying, and Interpreting. The researcher used six indicators from Learning Situation Analysis with the following results; 1) Hotel accommodation students learn English to be able to fluently communicate with local guests and foreigners. 2) Hotel accommodation students need diverse learning activities that can fulfill their purpose of learning English. 3) Hotel Accommodation Students' want teachers who understand their needs and can fulfill them. 4) The majority of Hotel Accommodation Students' use Minang as their mother tongue, making it difficult to speak English. 5) Hotel accommodation students' want a comfortable and quiet place with complete facilities to study. 6) Hotel accommodation students' choose to learn English in the morning with a duration of no more than 2 hours/day and more than once a week. From the above results it can be concluded that Target Situation Analysis can help teachers know the desire of hospitality accommodation students in learning English. So teachers should do a needs analysis before teaching.Kata kunci: Target Situation Analysis, Hotel Accommodation Students’